Application of simulation to freestyle aerial skiing - Yeadon, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The aim of this study was to use a computer simulation model of aerial movement to investigate the ability of asymmetrical arm movements to initiate twist in the flight phase of a triple layout somersault in the aerials event of freestyle skiing. Three arm movements were analysed resulting in triple somersaults with four and five twists together with lead up movements with one twist less. It is concluded that four twists can be initiated during flight using two phases of asymmetrical arm movement and that the production of five twists requires three phases of asymmetrical arm movement.